Penyuluhan Seputar Monosodium Glutamat di Pondok Pesantren Jamilurrahman Bantul - Arviani, Arviani (ABDIMAS Madani, 2024)
The Jamilurrahman Putri As-Salafy Islamic Boarding School is located in Wirokerta Village, Banguntapan Subdistrict, Bantul Regency. This boarding school operates under the auspices of the At-Turots Al-Islami Foundation. The students, predominantly girls, require education on food additives, particularly Monosodium Glutamate (MSG), to enhance the taste of food. The use of this additive is widely known and commonly used in the community, often referred to as 'micin.' The growing negative perception in society regarding MSG as a cause of cancer and other sources claiming its adverse health effects has led to concerns. This community service aims to provide education to the students that MSG is a safe food additive, and its usage is based on the recommended daily maximum intake. The community service approach employed is a community-based, directed forum discussion. The counseling activities are designed to impart additional knowledge about MSG to the female students of Jamilurrahman Putri Islamic Boarding School.